Suggested: y=x^2+1 graph - y=x^2+1 - y=log(x+√(x^2+1)) prove that - y=sin^-1(1-x^2/1+x^2) - y=cos^-1(1-x^2/1+x^2) find dy/dx - y=log(x+√(x^2+1)) find yn(0) - y^2-2pxy+p^2(x^2-1)=m^2 - y=sec inverse 1/2 x^2-1 - y=(1+x)(1+x^2)(1+x^4)(1+x^8) find dy/dx - y=(x^2-1)^n nth derivative - y=x^2-14x+22 - (d^3-d^2-6d)y=x^2+1 - verify that x3+y3+z3-3xyz=1/2(x+y+z) (x-y)2+(y-z)2+(z-x)2 - 3x/2-5y/3=-2 x/3+y/2=13/6 by substitution method - y=x^2+1 Browse related:
privacy contact
Copyright 2017 bapse
bapse is powered by Google and Youtube technologies
Thank you, for using bapse.
This site was designed and coded by Michael DeMichele,
and is being used as a portfolio demonstration. View more.